Characteristics of a Reciprocating Pump for Low-Cost Sustainable Water Hydraulic Technology Demonstrator (Journal of Engineering and Health Sciences, 2017)
An investigation on water-based reciprocating triplex piston pump is being conducted, as a low cost solution in substituting traditional oil hydraulics to water hydraulics. Triplex pumps are used in applications that require continuous pumping, and generally are capable of handling a wide range of fluid types, including corrosive fluids, abrasive fluids, and slurries containing relatively large particulates. Thus, an evaluation by using simple simulation process has been conducted on the volumetric efficiency, in order to understand its ability in energy-efficient system. In this paper, the results of a simulated study on a positive displacement triplex piston pump are presented. The result concludes that the use of water is relatively efficient if the slip factor is maintained to 0.003, with system pressure from 10 to 40 bar.